Obstructing Chiari Network Facilitating Blood Flow Across a Patent Foramen Ovale Causing Hypoxia - Rimmy Garg, MD; Tyler Wark, MD; John Dudley, MD; James Robertson, MD (JACC: Case Reports, 2020)
A 36-year-old man with progressive dyspnea and hypoxia was found to have a large, partially fenestrated Chiari network accelerating blood flow through a patent foramen ovale with preservation of an embryonic right-to-left atrial flow pattern. He underwent successful percutaneous patent foramen ovale closure with resolution of his exertional symptoms. (Level of Difficulty: Beginner.)